Construction of an Upconversion Nanoprobe with Few‐Atom Silver Nanoclusters as the Energy Acceptor1. (5th March 2015) - Xiao, Yan; Zeng, Lingyu; Xia, Tian; Wu, Zhengjun; Liu, Zhihong
Abstract Herein we report that few‐atom silver nanoclusters (Ag NCs) can be effective energy acceptors for upconversion phosphors (UCPs). A luminescence resonance energy transfer (LRET) probe for biothiols was constructed by decorating UCPs with dithiol‐stabilized Ag NCs. Owing to the unique properties of ultrasmall NCs, properties which bridge the gap between those of small molecules and those of nanoparticles, the use of approximately 1.9 nm Ag NCs as energy acceptors endows the probe with high energy‐transfer efficiency, good biocompatibility, and flexibility. The UCP–Ag NC nanoprobe enables rapid and robust target assay in solutions. It was also uploaded into living cells and used to detect intracellular biothiol levels with high discrimination. Moreover, the probe shows transportability in vivo and can be used for tissue imaging. The facile growth of few‐atom metal NCs on diverse templates may enable the development of various nanoprobes combining UCPs and metal NCs.